Can Topical Calcipotriol Be a Treatment Alternative in Actinic Keratoses? A Preliminary Report - (:unkn) unknown (JOURNAL OF DRUGS IN DERMATOLOGY, 2009)
Background: Recent research demonstrated that vitamin D, apart from calcium-related actions, has antiproliferative, prodifferentiative and immunomodulatory activities. Objective: To determine whether actinic keratoses may benefit from the antiproliferative and prodifferentiative effects of topical vitamin D. Materials and Methods: The study was an investigator-blinded, half-side comparison trial. Patients applied calcipotriol cream to one side and Ultrabase (R) cream as placebo to the other side of the scalp and/or face for 12 weeks. The total number of actinic keratoses (AKs), diameters and total scores of the target lesions were determined at each visit. Results: Nine patients were included, eight of whom completed the treatment. There was a statistically significant difference between the total number of AKs at baseline and at week 12 on calcipotriol applied side whereas no difference was detected on placebo applied side (p=0.028 vs p=1.00). The mean total score of the target lesions reduced significantly at week 12 on calcipotriol side; however, no significant reduction was found on placebo side (p=0.017 vs p=0.056). Although side effects were more common on calcipotriol side, the difference was not statistically significant. Conclusion: Topical calcipotriol may show promise in the treatment of actinic keratoses. More studies are needed to confirm its efficacy.
Keywords: T-CELL LYMPHOMA; VITAMIN-D; ADVANCED BREAST; CANCER; CALCITRIOL; ISOTRETINOIN; COMBINATION; ANALOGS